Durability and cross-reactivity of immune responses induced by a plant-based virus-like particle vaccine for COVID-19 - Philipe Gobeil; Stéphane Pillet; Iohann Boulay; Nathalie Charland; Aurélien Lorin; Matthew P. Cheng; Donald C. Vinh; Philippe Boutet; Robbert Van Der Most; François Roman; Maria Angeles Ceregido; Nathalie Landry; et al. (Nature Communications, 2022)
Here, the authors report results from a Phase 1 trial with an AS03-adjuvanted, plant-based virus-like particle displaying the spike protein of the ancestral SARS-CoV-2. Six months post-second dose, they observe good neutralizing antibody titers and T cell responses to ancestral virus and variants of concern in participants.